The Impact of Mangrove Forest Management on the Community in Poton Bako Hamlet, Jerowaru Village, East Lombok Regency - Bayu, Teza Haikal; Eko, Danil; Karimatunnisa, Gina; Khairunnisah, Noni Antika; Sari, Ni Kadek Wahyuni Merta (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
This research aims to: determine Mangrove Forest Management Patterns and the Impact on the Community in Poton Bako Hamlet, Jerowaru Village, East Lombok Regency. This research applies a qualitative approach with a case study method. The data collection techniques applied in this research are interviews, observation and documentation. The data analysis techniques in this research are data reduction, data presentation and drawing conclusions. The results of the research explain that (1) Mangrove Forest Conservation Pattern in Poton Hamlet, Jerowarau Village, namely the Mangrove Ecotourism Development Pattern (managers together with the community clean the mangrove forest from rubbish that has accumulated in the mangrove forest area to be developed into mangrove tourism), Mangrove Ecosystem Rehabilitation Pattern (manager creating a small-scale nursery area to create a stock of mangrove seeds for replanting), Mangrove Ecosystem Conservation Pattern (the management forms Pokmaswas members with the aim of acting as supervisors to prevent illegal felling of mangrove trees). (2) The impact of managing the mangrove forest for the community in Poton Bako hamlet is a positive impact (creating new jobs for the people of Poton Bako hamlet; increasing the economic income of the community by managing the mangrove forest into a tourist spot and a place to sell SME products such as mangrove coffee, mini-boats/ boats and clothes typical of Bale Mangrove tourism; catches of Poton Bako hamlet fishermen have increased and if the weather is not conducive to going to sea, fishing communities can look for shrimp, fish and crabs in the mangrove forest area; the community has received education and increased public awareness to protect the mangrove forest area. ; the coastal area of Poton Bako hamlet is protected from abrasion and prevents sea water intrusion onto land